1985
DOI: 10.1177/00220345850640090201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inflammation on the of Collagen Types, I, III, IV, and V and Type I Trimer and Fibronectin in Human Gingivae

Abstract: DleI pt et s oI.eS f Pathologv and o -'eriodollicis, and Cel terf' for Researchl i Oral I.,log .,UfIieri l o.fI IX \\,'t.fI1,inI"toll School of5Mediif , Seattle, Washinigton 9S/9-5 le effect of' in/flammttillon oil leit distribution f 'collag'tzens types I, I, IV, and V and Istype' 1 i/ I trier tdilnonecutiln ilihuman 14,i/gilvat w'.as studied s (/er staining 1th1('m withl anti bodies to these )rotein.s. Ginltival antibodies, and l staining was visualized by ifndirct itmmiune fluor estcene using FITCi or rholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…The expression of the laminin receptor by these epithehal cells does not underline that they were the target for a cytotoxic immune reaction. Whereas the integrins in OLP showed a more non-specific pattern typical for a chronic inflammatory reaction, the most intense changes of the ECM pattern as compared with normal oral mucosa were noted in the subepithehal connective tissue, resembling the pattern of severe inflammation observed in gingivitis (34). This loss of ECM proteins, especially in the atrophic variant of OLP, is probably due to cytokines released from immunocompetent cells such as interferon y and TNFalpha that induce the expression of collagenases and that are found in LP (3,35).…”
Section: Discussionmentioning
confidence: 87%
“…The expression of the laminin receptor by these epithehal cells does not underline that they were the target for a cytotoxic immune reaction. Whereas the integrins in OLP showed a more non-specific pattern typical for a chronic inflammatory reaction, the most intense changes of the ECM pattern as compared with normal oral mucosa were noted in the subepithehal connective tissue, resembling the pattern of severe inflammation observed in gingivitis (34). This loss of ECM proteins, especially in the atrophic variant of OLP, is probably due to cytokines released from immunocompetent cells such as interferon y and TNFalpha that induce the expression of collagenases and that are found in LP (3,35).…”
Section: Discussionmentioning
confidence: 87%
“…Narayanan & Page (1983b) have shown that though total collagen content of the gingiva fell sharply, the proportions of eollagens type I and III remain roughly constant in disease, whilst collagen type V increases markedly. Narayanan et al (1985) also identify the appearance of a unique type I collagen trimcr (composed of three a chains) in inflamed gingiva. Ko et al (1977) showed a sub-population of fibroblasts which were selectively inhibited in terms of growth and synthetic activity by prostaglandin E, (PGE2) though how this effect is mediated is unelear.…”
Section: Connective Tissue Dynamics and Repairmentioning
confidence: 85%
“…It has been found in inflamed tissues and in the first stages of healing. 44,45 This kind of extracellular matrix formation may be of importance in wound-healing processes because of the matrix stability in collagenolytic mechanisms by bacteria.…”
Section: Discussionmentioning
confidence: 99%